2021
DOI: 10.1136/bmjopen-2021-055635
|View full text |Cite
|
Sign up to set email alerts
|

Effects of turnover and stability of health staff on quality of care in remote communities of the Northern Territory, Australia: a retrospective cohort study

Abstract: ObjectivesTo evaluate the relationship between markers of staff employment stability and use of short-term healthcare workers with markers of quality of care. A secondary objective was to identify clinic-specific factors which may counter hypothesised reduced quality of care associated with lower stability, higher turnover or higher use of short-term staff.DesignRetrospective cohort study (Northern Territory (NT) Department of Health Primary Care Information Systems).SettingAll 48 government primary healthcare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 25 publications
0
8
0
1
Order By: Relevance
“…In our analysis, the Australian PHC delivery is comprehensive that it provides a wide range of services for a variety of target populations. In terms of the ranges of services, Australian PHC assess and deal with social determinants and / or risk factors [17,24,25,30,36,45,48,53,62,63,65,90,98,99,125], acute and chronic diseases [27,47,52,59,81,82,84,96,97,101,104,105,108,110,111,114,117,118,120 ], mental health [26,46,61,68,126,132], cancer and palliative care including aged care [43,86,103,122], pharmacy and medication safety [35,107], evidence-based practice and knowledge translation [55,…”
Section: Comprehensivenessmentioning
confidence: 99%
See 2 more Smart Citations
“…In our analysis, the Australian PHC delivery is comprehensive that it provides a wide range of services for a variety of target populations. In terms of the ranges of services, Australian PHC assess and deal with social determinants and / or risk factors [17,24,25,30,36,45,48,53,62,63,65,90,98,99,125], acute and chronic diseases [27,47,52,59,81,82,84,96,97,101,104,105,108,110,111,114,117,118,120 ], mental health [26,46,61,68,126,132], cancer and palliative care including aged care [43,86,103,122], pharmacy and medication safety [35,107], evidence-based practice and knowledge translation [55,…”
Section: Comprehensivenessmentioning
confidence: 99%
“…Table S2 in the Online Supplementary Document describes characteristics of 15 studies [26,35,52,60,82,10 5,107,112,113,115,117,123,124,129,130] conducted on quality of care and its attributes (including continuity of care, effectiveness, and safety). Of these studies, seven reported quality of care [26,52,82,105,112,113,124], three described the effectiveness of different interventions to ensure the quality of care [117,129,130] and two studies reported continuum of care [60,115]. There are several factors including client or system factors [52,105] affecting the quality of care.…”
Section: Quality Of Carementioning
confidence: 99%
See 1 more Smart Citation
“…There are also a range of factors associated with the recruitment and retention of healthcare staff to remote areas including being of rural origin, completion of training in a rural location, the lifestyle that is offered in remote areas, playing a role in improving Aboriginal and Torres Strait Islander health, and adequate access to resources and support for the family of the health professional (e.g., childcare, education for children) [12][13][14][15]. Anecdotally, there is a commonly held belief that there is a relationship between continuity of care and a stable workforce, but there is little evidence to support this, as is demonstrated by Jones and colleagues [16]. Securing a health workforce to provide culturally appropriate and evidence-based, clinically sound care for Aboriginal peoples in remote regions has been difficult [17].…”
Section: Introductionmentioning
confidence: 99%
“…Os últimos resultados podem refletir o acaso, mas também podem indicar fatores contextuais dos serviços que atenuem os potenciais efeitos negativos da diminuição da estabilidade da força de trabalho e aumento da rotatividade médica. (112) Outro estudo de coorte retrospectivo conduzido nos Estados Unidos com 359.470 usuários do Medicare entre 2008 e 2017, com objetivo de analisar o impacto do desligamento de médicos na APS (Primary Care Physicians: geriatras, médicos de família, pediatras, ginecologistas e obstetras), mostrou que a perda da continuidade se relacionou negativamente com a qualidade dos serviços de saúde, associando-se a uma queda de 6% do total de vacinados; diminuição em 18% do uso de serviços de APS; aumento em 6% das visitas às demais especialidades médicas e em 18% aos serviços de urgência e emergência. (27) Além de fatores contextuais, como características da região e dos serviços de APS, que poderiam explicar os diferentes resultados encontrados na literatura, é possível supor que o impacto da rotatividade nos serviços também se relacione ao perfil da força de trabalho.…”
Section: Organizaçõesunclassified